Reference values for volume, fat content and shape of the hip abductor muscles in healthy individuals from Dixon MRI - Belzunce, Martin A.; Henckel, Johann; Di Laura, Anna; Hart, Alister J. (NMR in biomedicine, 2022)
Healthy hip abductor muscles are a good indicator of a healthy hip and an active lifestyle, as they are greatly involved in human daily activities. Fatty infiltration and muscle atrophy are associated with loss of strength, loss of mobility and hip disease. However, these variables have not been widely studied in this muscle group. We aimed to characterize the hip abductor muscles in a group of healthy individuals to establish reference values for volume, intramuscular fat content and shape of this muscle group. To achieve this, we executed a cross‐sectional study using Dixon MRI scans of 51 healthy subjects. We used an automated segmentation method to label GMAX, GMED, GMIN and TFL muscles, measured normalized volume (NV) using lean body mass, fat fraction (FF) and lean muscle volume for each subject and computed non‐parametric statistics for each variable grouped by sex and age. We measured these variables for each axial slice and created cross‐sectional area and FF axial profiles for each muscle. Finally, we generated sex‐specific atlases with FF statistical images. We measured median (IQR) NV values of 12.6 (10.8‐13.8), 6.3 (5.6‐6.7), 1.6 (1.4‐1.7) and 0.8 (0.6‐1.0) cm3/kg for GMAX, GMED, GMIN and TFL, and median (IQR) FF values of 12.3 (10.1‐15.9)%, 9.8 (8.6‐11.2)%, 10.0 (9.0‐12.0)% and 10.2 (7.8‐13.5)% respectively. FF values were significantly higher for females for the four muscles (p < 0.01), but there were no significant differences between the two age groups. When comparing individual muscles, we observed a significantly higher FF in GMAX than in the other muscles. The reported novel reference values and axial profiles for volume and FF of the hip abductors, together with male and female atlases, are tools that could potentially help to quantify and detect early the deteriorating effects of hip disease or sarcopenia. We characterized the hip abductor muscles from 51 healthy subjects that underwent Dixon MRI. Reference values for volume and fat infiltration, axial profiles and atlas images for fat content are presented. These data sets can be used as a reference for healthy abductors in clinical research and to develop novel tools for a comprehensive and automated assessment of this muscle group.